2022
DOI: 10.3389/fphar.2022.817673
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Application of Population Pharmacokinetic Models for Identifying Delayed Methotrexate Elimination in Patients With Primary Central Nervous System Lymphoma

Abstract: Objective: Several population pharmacokinetic (popPK) models have been developed to determine the sources of methotrexate (MTX) PK variability. It remains unknown if these published models are precise enough for use or if a new model needs to be built. The aims of this study were to 1) assess the predictability of published models and 2) analyze the potential risk factors for delayed MTX elimination.Methods: A total of 1458 MTX plasma concentrations, including 377 courses (1–17 per patient), were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The model proposed by Mao et al showed superior accuracy (MDPE 19.25%), but did not meet the other standard. 9 For other evaluation indicators, none of the models met all the criteria (MDPE% ≤ ±20%, MAPE% ≤ 30%, F 20 ≥ 35%, and F 30 ≥ 50%). B-A plots of the population prediction showed that all models exhibited an apparent trend of undervaluation (Figure 1), with a mean range of −102.8% to −24.28%.…”
Section: Prediction-based Diagnosticsmentioning
confidence: 94%
See 4 more Smart Citations
“…The model proposed by Mao et al showed superior accuracy (MDPE 19.25%), but did not meet the other standard. 9 For other evaluation indicators, none of the models met all the criteria (MDPE% ≤ ±20%, MAPE% ≤ 30%, F 20 ≥ 35%, and F 30 ≥ 50%). B-A plots of the population prediction showed that all models exhibited an apparent trend of undervaluation (Figure 1), with a mean range of −102.8% to −24.28%.…”
Section: Prediction-based Diagnosticsmentioning
confidence: 94%
“…In a recent article, 8 previously published models for HDMTX in adults were validated using goodness of fit (GOF) and VPCs. 9 We validated a total of 7 models, with 4 of them overlapping with those in the aforementioned article. The remaining 3 models had not been previously validated.…”
Section: Npde and Vpcs Are 2 Commonly Used Methodsmentioning
confidence: 99%
See 3 more Smart Citations